1979
DOI: 10.1007/bf01317559
|View full text |Cite
|
Sign up to set email alerts
|

Determination of antibodies against cytomegalovirus-induced early antigens by using rabbit lung fibroblasts

Abstract: The determination of antibodies against cytomegalovirus-induced antigens in 30 patients with acute cytomegalovirus infection and in 100 healthy control persons, using early antigen preparations of human lung fibroblasts and of rabbit lung fibroblasts, yielded results showing a high degree of agreement. For such investigations, however, the use of rabbit cells proved to be of advantage because the preparation of the early antigens can be carried out without inhibition of the DNA synthesis of the host cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

1983
1983
1985
1985

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…The detection by EID of antibody to LTA in all sera from excretors, of antibody to EA in most of them (16 of 22), and of persistence of both antibodies for several years (Table 11), is in general accord with results obtained by others using a variety of serologic techniques [The et al, 1977;Gerna et al, 1978;Farber et al, 1979;Michelson et al, 1979b;Ohtsuka et al, 1979;Griffiths et al, 1980;Friedman et al, 19821. Similarly, EID results were largely consistent with those in our own CF, IHA, and IIF-EA tests, although EID appears to be less sensitive in detecting low levels of antibody to both EA and LTA in sera from apparently healthy, nonexcretors.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The detection by EID of antibody to LTA in all sera from excretors, of antibody to EA in most of them (16 of 22), and of persistence of both antibodies for several years (Table 11), is in general accord with results obtained by others using a variety of serologic techniques [The et al, 1977;Gerna et al, 1978;Farber et al, 1979;Michelson et al, 1979b;Ohtsuka et al, 1979;Griffiths et al, 1980;Friedman et al, 19821. Similarly, EID results were largely consistent with those in our own CF, IHA, and IIF-EA tests, although EID appears to be less sensitive in detecting low levels of antibody to both EA and LTA in sera from apparently healthy, nonexcretors.…”
Section: Discussionsupporting
confidence: 87%
“…3), together with detection of only six LA in EID when a similar extraction buffer was used by Schtnitz et a1 (1980), indicate that one or more of the buffer components alters the antigens in such a way that multivalent binding of antibody, required for lattice formation in EID, is impaired. Such alterations would be of less significance in conventional immunoprecipitation when much smaller complexes of antigen and antibody are detected by ultracentrifugation or by adsorption to protein A [Michelson et al, 1979a;Blanton and Tevethia, 19811. The detection by EID of antibody to LTA in all sera from excretors, of antibody to EA in most of them (16 of 22), and of persistence of both antibodies for several years (Table 11), is in general accord with results obtained by others using a variety of serologic techniques [The et al, 1977;Gerna et al, 1978;Farber et al, 1979;Michelson et al, 1979b;Ohtsuka et al, 1979;Griffiths et al, 1980;Friedman et al, 19821. Similarly, EID results were largely consistent with those in our own CF, IHA, and IIF-EA tests, although EID appears to be less sensitive in detecting low levels of antibody to both EA and LTA in sera from apparently healthy, nonexcretors.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Results of some studies have indicated that antibody responses to the early antigens of Epstein-Barr virus and human cytomegalovirus are of short duration, and that the presence of antibodies to these antigens is suggestive of active infections with the viruses Henle et al, 1971;The et al, 19741. However, more recent studies have cast doubt upon the diagnostic significance that can be attached to the presence of antibodies to early antigens of these viruses, since such antibodies have been demonstrated in individuals without evidence of active viral infections [Farber et al, 1979;Favart et al, 1978;Friedman et al, 1982;Gerna et al, 1979;Gotlieb-Stematsky et al, 1978;Griffiths et al, 1980;Kurstak et al, 19781. One study has been reported in which antibodies to early antigens of varicella-zoster virus (VZV) were demonstrable only in varicella or herpes zoster infections, and were considered to be markers of current VZV infection [Gerna et al, 19791.…”
Section: Introouctionmentioning
confidence: 97%
“…Results of some studies have indicated that antibody responses to the early antigens of Epstein-Barr virus and human cytomegalovirus are of short duration, and that the presence of antibodies to these antigens is suggestive of active infections with the viruses Henle et al, 1971;The et al, 19741. However, more recent studies have cast doubt upon the diagnostic significance that can be attached to the presence of antibodies to early antigens of these viruses, since such antibodies have been demonstrated in individuals without evidence of active viral infections [Farber et al, 1979;Favart et al, 1978;Friedman et al, 1982;Gerna et al, 1979;Gotlieb-Stematsky et al, 1978;Griffiths et al, 1980;Kurstak et al, 19781. One study has been reported in which antibodies to early antigens of varicella-zoster virus (VZV) were demonstrable only in varicella or herpes zoster infections, and were considered to be markers of current VZV infection [Gerna et al, 19791. The present investigation on antibody responses to early antigens of VZV and herpes simplex virus (HSV) was undertaken with the following aims: (1) to explore further antibody responses to early antigens of VZV and HSV in primary, reactivated, and latent infections in efforts to determine the diagnostic significance that should be attached to these antibody responses, (2) to determine whether the serodifferentiation of VZV and HSV infections might be improved through the use of early antigen preparations, (3) to determine whether early antigens produced with different blocking agents might differ in their serological reactivity, and (4) to study the reactivity of class-specific viral antibodies with early antigens of VZV and HSV.…”
Section: Introouctionmentioning
confidence: 99%